Who takes care of the burden of emotions in palliative care workers? A study with the job demands-resources perspective - Giulia Sciotto; Francesca Sinatra; Cristina Moavero; Francesco Pace (BMC Psychology)
Abstract Background This study aims to investigate the risks and challenges that palliative care workers face in their daily work and their relationships with a source of stress typically associated with working closely with end-of-life issues: compassion fatigue, a condition of emotional exhaustion, cynicism, and impaired ability to feel empathy. The Job Demands-Resources (JD-R) model was used as a theoretical framework to understand and interpret the relationships between individual and work demands and resources of palliative care professionals with their perceptions of well-being and their levels of compassion fatigue. Specifically, we focused on surface acting (the need to manipulate the expression of one’s real emotions), emotional self-efficacy, and the perceived meaningfulness attributed to work. We hypothesized that compassion fatigue was positively related to job demand and negatively related to job resources. Conversely, we hypothesized that perceived well-being was positively associated with job resources and negatively associated with job demand. Methods The sample consisted of 236 palliative care workers (physicians, nurses, social and health workers, psychologists) from facilities distributed throughout Italy. The structural equation modeling (SEM) technique was used. Results The results confirmed the hypothesized protective role of the meaningfulness of work and emotional self-efficacy, and the detrimental role of surface acting. Conclusions With the present study, we aim to contribute to a better understanding of how to support the psychological and physical well-being of those who devote their professional lives to providing care and comfort to terminally ill individuals.